How the Eyes Connect to the Heart: The Influence of Eye Gaze Direction on Advertising Effectiveness - To, Rita Ngoc; Patrick, Vanessa M (Journal of Consumer Research, 2021)
AbstractA model’s eyes are a powerful and ubiquitous visual feature in virtually any advertisement depicting a person. But does where the ad model’s eyes look matter? Integrating insights from social psychology and performance and visual art theory, we demonstrate that when the ad model’s gaze is averted (looking away from the viewer), the viewer is more readily transported into the ad narrative and responds more favorably to the ad than when the ad model’s gaze is direct (looking directly at the viewer). Five multi-method experiments (field and lab studies) illustrate that averted gaze (direct gaze) enhances narrative transportation (spokesperson credibility) to boost the effectiveness of emotional (informative) ads. Study 1 is a Facebook field study that demonstrates the effect of averted (vs. direct) gaze direction on advertising effectiveness using a real brand. Studies 2a and 2b implicate enhanced narrative transportation as the underlying process mechanism by measuring (study 2a) and manipulating (study 2b) narrative transportation. Studies 3a and 3b examine ad contexts in which direct gaze can enhance ad effectiveness: when the ad has informational (vs. emotional) appeal (study 3a), and when the viewer prefers not to identify with the negative emotional content of the ad (study 3b).